Is three day-of-the-week effect in the Malaysian stock market? - Othman Yong,; Ismail Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 1999)
This paper looks at the issue of day-of-the-week effect in the case of the Malaysian stock market, which is an emerging stock market in the Asia-Pacific region. The study covers a period between January 1989 and December 1993, using all major indices of the KLSE. Overall, there seems to be an abnormally high return on Fridays, and a low return on Monday, a pattern quite consistent with markets in the West. However, from statistical point of view, this phenomenon is not significant, i.e., the Malaysian stock market is still efficient in the weak sense of the efficient market hypothesis. Our results are in contradiction with those of an earlier study by Md. Nasir and Mohamed (1987) which find that the day-of-the-week disappears after the implementation of the new settlement procedure, calle Fixed Delivery and Settlement System (FDSS) beginning in January 1990